Actualizing children's rights through early childhood care and education: A focus on the Caribbean. (March 2020) - Kinkead-Clark, Zoyah; Burns, Sheron; Abdul-Majied, Sabeerah
The vast majority of the islands in the Anglophone Caribbean ratified the Convention of the Rights of the Child shortly after its adoption by the United Nations in 1989. In this piece, we examine how the articulation of the Convention of the Rights of the Child in the Caribbean has shaped early childhood care and education. We note that though significant strides have been made, approximately 30 years after the ratification of the Convention on the Rights of the Child, many Anglo-Caribbean islands continue to struggle to fulsomely ensure children's access to all their fundamental rights. This conceptual article presents a historical overview of the implementation of specific Articles of the Convention of the Rights of the Child in the Caribbean. How these Articles have shaped the policies and practices guiding early education across the region is also explored. We conclude that though much has been achieved, as a region, more progress is needed to ensure that all children have equal opportunities to fulfil their rights.